Дослідження ефективності та оптимізації технологій міжпроцесної взаємодії у серверних додатках - Свєтлінський, О. А. (ХНУРЕ, 2024)
This work aims to research and analyze the efficiency and optimization of existing interprocess interaction technologies, specifically the mechanisms provided by an operating system, and to select criteria for this research. The focus of the study is on the technology of interprocess interaction during data transfer within a single system, specifically a server application. The existing technologies and protocols for inter-process data transfer were evaluated, including their features, advantages, and disadvantages, as well as their working principles. Methods of comparison were described and demonstrated, and formulas for calculating numerical indicators were proposed as a result of this work.
Keywords: міжпроцесні взаємодії; серверні додатки